Peran Konten Pada Hashtag #Wenanampohon Dalam Meningkatkan Kesadaran Peduli Lingkungan Pada Pengikut Tiktok Jerhemynemoo Di Kota Padang - Gustianda Yelian Putra; Ria Edlina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This thesis will focus on the role of content on the hashtag of #WenanamPohon in increasing environmental awareness among Jerhemynemoo’s tiktok followers in Padang City. The hashtag #WenanamPohon is content on social media created by Jerhemynemoo which aims to preserve the environment with a movement to plant 10,000 trees by inviting his followers to participate in the program. The purpose of this study is to determine how the content on the hashtag #WenanamPohon created by Jerhemynemoo on his TikTok social media influences environmental awareness among his TikTok social media followers. The theory used in this study is constructivism theory. The method used in this study is descriptive qualitative, this method is used to collect data related to the content on the hashtag #WenanamPohon and its impact on environmental awareness. The data used in this study were obtained from the results of in-depth interviews with predetermined informants. The data in this study were tested using data source triangulation. Based on the results of this study, the main role of the content on the hashtag #WenanamPohon in increasing environmental awareness among Jerhemynemoo followers is, first as educational content, this content contains knowledge about the environment. Second as a relationship enhancer, by participating in planting this tree, his followers establish relationships with each other. Third is to build interaction, Jerhemynemoo in the content with the hashtag #WenanamPohon invites all social media users, both his followers and not, to jointly realize this tree planting program so that his followers are aware of the importance of caring for the environment. Fourth is to build trust, several videos on the hashtag #WenanamPohon explain that every 15 videos shared will become 1 tree seedling to be planted, and Jerhemynemoo realizes this by planting 10,000 trees.